Adaptasi Industri Perjalanan Wisata Bali Ditengah Anomali Kebijakan Menyambut Era Kenormalan Baru - Ida Bagus Gowinda; Dyah Mutiarin; Janianton Damanik (Pusaka: Journal of Tourism, Hospitality, Travel and Business Event, 2022)
According to UNWTO (2020), during the pandemic period there was a significant decline in the tourism sector, such as travel and hospitality. This condition occurs throughout the country, including on the island of Bali as a world tourist destination. During the COVID-19 pandemic, Bali's economic dependence on the tourism industry was felt. Coupled with policies that continue to change along with scientific developments related to COVID-19 and efforts to deal with it, the tourism industry inevitably has to 'adapt' more quickly. This article attempts to describe government policies that have had an impact on the travel industry, especially in Bali. The government policy that is being studied is the policy published in the first and second quarters of 2020. The data collection method is carried out only by literature review. The discussion is presented in a descriptive-qualitative nature, and is critically reviewed on the phenomena depicted from secondary data and documentations of pre-existing research on the same topic. The results found that the Indonesian government's policy is absolute to be used as a reference for the travel industry sector to clean up and adapt to developments in handling COVID-19 even though the related policies always change from time to time with dynamism.